Concomitant alterations of metabolic parameters, cardiovascular risk factors and altered cortisol secretion in patients with adrenal incidentalomas during prolonged follow‐up. (25th January 2017) - Papanastasiou, Labrini; Alexandraki, Krystallenia Ι.; Androulakis, Ioannis I.; Fountoulakis, Stelios; Kounadi, Theodora; Markou, Athina; Tsiavos, Vaios; Samara, Christianna; Papaioannou, Theodoros G.; Piaditis, George; Kaltsas, Gregory
Summary: Objective: Adrenal incidentalomas (AI) are associated with metabolic and hormonal abnormalities, most commonly autonomous cortisol secretion (ACS). Data regarding alterations of insulin resistance (IR) and ACS after prolonged follow‐up are limited. We investigated the evolution of IR, cortisol secretion and ACS development in patients with AI during prolonged follow‐up. Design: Prospective study in a tertiary hospital. Patients and measurements: Seventy‐one patients with AI [51 nonfunctioning (NFAI) and 20 ACS] and 5·54 ± 1·7 years follow‐up underwent testing for ACS and oral glucose tolerance test to determine IR indices and adrenal imaging. Results: At follow‐up, 16/51 (31%) NFAI patients converted to ACS, while two with previous ACS reverted to NFAI; 21% (7/33) of patients who did not covert to ACS exhibited high urinary‐free cortisol (H‐UFC) levels. All AI patients developed deterioration of IR irrespective of their cortisol secretory status. Eight patients developed newly diagnosed type 2 diabetes (9·8% NFAI and 15% ACS, respectively) and 14 IR (17·6% NFAI and 25% ACS, respectively). Adenoma size increased from 2·1 ± 0·8 to 2·3 ± 0·8 cm, whereas IR correlated with postdexamethasone cortisol level and adenoma size increase. IR showed an incremental continuum trend from normal UFC (Ν‐UFC), to H‐UFC, C‐ACS and ACS patients. Conclusions: New‐onset ACS developed in 31% patients with NFAI, whereas 21% of NFAI patients had H‐UFC levels. All AI patients as a group and the subgroups of N‐UFC, H‐UFC, C‐ACS and ACS patients developed deterioration of metabolic parameters during follow‐up that was more prominent in ACS patients.